2012
DOI: 10.4161/psb.7.1.18636
|View full text |Cite
|
Sign up to set email alerts
|

Reduced levels of class 1 reversibly glycosylated polypeptide increase intercellular transport via plasmodesmata

Abstract: Maize and Arabidopsis thaliana class 1 reversibly glycosylated polypeptides ( C1 RGPs) are plasmodesmata-associated proteins. Previously, overexpression of Arabidopsis C1 RGP AtRGP2 in Nicotiana tabacum was shown to reduce intercellular transport of photoassimilate, resulting in stunted, chlorotic plants, and inhibition of local cell-to-cell spread of tobacco mosaic virus (TMV). Here, we used virus induced gene silencing to examine the effects of reduced levels of Plasmodesmata Structure and FunctionPlasmodes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
2
12
0
Order By: Relevance
“…First, a search was performed using “plasmodesmata” in the gene description and GO terms of AgNP and/or Ag + affected genes, which were obtained from BioMart [ 150 ]. Second, a list of genes that are directly related to plasmodesmata was prepared based on GO terms in AmiGO2 [ 146 , 151 , 152 , 153 , 154 ], GONUTS (the Gene Ontology Normal Usage Tracking System [ 155 ], and literature search [ 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ]. Altogether, a list of the 26 plasmodesmata related genes was collected and it was provided in Table S13 .…”
Section: Methodsmentioning
confidence: 99%
“…First, a search was performed using “plasmodesmata” in the gene description and GO terms of AgNP and/or Ag + affected genes, which were obtained from BioMart [ 150 ]. Second, a list of genes that are directly related to plasmodesmata was prepared based on GO terms in AmiGO2 [ 146 , 151 , 152 , 153 , 154 ], GONUTS (the Gene Ontology Normal Usage Tracking System [ 155 ], and literature search [ 156 , 157 , 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 ]. Altogether, a list of the 26 plasmodesmata related genes was collected and it was provided in Table S13 .…”
Section: Methodsmentioning
confidence: 99%
“…One lower leaf per plant was syringe infiltrated with fresh overnight cultures of Agrobacterium resuspended in infiltration media (10 mM MgCl 2 , 10 mM MES, and 200 μM acetosyringone, pH 5.6) to a final OD 600nm = 0.5. Three Agrobacterium cultures were used that carried T-DNA encoding either TMV-GFP (Liu et al , 2002; Burch-Smith et al , 2012), PVX-GFP (Peart et al , 2002), or a mock control. All plants were photographed seven days post agroinfiltration under a long wave UV lamp (100 watt, 365 nm, 115V-60Hz).…”
Section: Methodsmentioning
confidence: 99%
“…Third, the deposition of calreticulin and reticulons in the DT lumen suggested by Knox et al leads to the expansion of the ER DT lumen [57]. Fourth, narrowing the Pd sleeves, as probably occurs through the participation of the actin-formin complex [70], as well as the accumulation of remorin [56], PDLP1 and 5 [75][76][77][78][79], GnTL [72], and C1 RGP [66][67][68]. Pd opening, as a process opposite to closing, can include (1) the removal of callose and (2) the displacement of negative regulators from the Pd structure.…”
Section: Mechanisms Of Pdap Participation In Intercellular Cytoplasmimentioning
confidence: 97%
“…Subsequently, this hypothesis was confirmed by experiments showing changes in the expression levels of the gene encoding At C1 RGP. It has been shown that At C1 RGP overexpression leads to a reduction in Pd permeability for photoassimilates and TMV cell-to-cell movement [68]; in contrast, reduced levels of At C1 RGP increase intercellular transport via Pd, and TMV exhibited accelerated systemic spread [66].…”
Section: Forminsmentioning
confidence: 99%